2022
DOI: 10.3390/ijms23137404
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Membrane Selectivity of Romo1-Derived Antimicrobial Peptide AMPR-22 via Molecular Dynamics

Abstract: The abuse or misuse of antibiotics has caused the emergence of extensively drug-resistant (XDR) bacteria, rendering most antibiotics ineffective and increasing the mortality rate of patients with bacteremia or sepsis. Antimicrobial peptides (AMPs) are proposed to overcome this problem; however, many AMPs have attenuated antimicrobial activities with hemolytic toxicity in blood. Recently, AMPR-11 and its optimized derivative, AMPR-22, were reported to be potential candidates for the treatment of sepsis with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In a study on AMPR11 and AMPR22 interacting with bacterial inner membranes, it was observed that AMPR22 adopted greater helicity by forming hydrogen bonds with cardiolipin. 185 On account of the heterogeneity in the chemical structure of bacterial outer membrane LPS molecules, the insertion barriers for antimicrobial peptides show variability across different regions of LPS. Free energy landscapes determined by Sharma and Ayappa for the antimicrobial peptide CM15 186 using umbrella sampling simulations indicated spontaneous penetration into the O-antigen region with a large barrier in the core saccharide region.…”
Section: ■ Surfactants As Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on AMPR11 and AMPR22 interacting with bacterial inner membranes, it was observed that AMPR22 adopted greater helicity by forming hydrogen bonds with cardiolipin. 185 On account of the heterogeneity in the chemical structure of bacterial outer membrane LPS molecules, the insertion barriers for antimicrobial peptides show variability across different regions of LPS. Free energy landscapes determined by Sharma and Ayappa for the antimicrobial peptide CM15 186 using umbrella sampling simulations indicated spontaneous penetration into the O-antigen region with a large barrier in the core saccharide region.…”
Section: ■ Surfactants As Antimicrobialsmentioning
confidence: 99%
“…Understanding the lipid-mediated changes in peptide conformation is an important aspect in the design of synthetic peptides. In a study on AMPR11 and AMPR22 interacting with bacterial inner membranes, it was observed that AMPR22 adopted greater helicity by forming hydrogen bonds with cardiolipin . On account of the heterogeneity in the chemical structure of bacterial outer membrane LPS molecules, the insertion barriers for antimicrobial peptides show variability across different regions of LPS.…”
Section: Translocation Of Antimicrobial Peptidesmentioning
confidence: 99%
“…Antibiotic resistance is a significant global public health threat, resulting in at least 1.27 million deaths worldwide in 2019 [ 1 ]. The misuse and overuse of antibiotics are the primary factors driving the development of drug-resistant strains [ 2 , 3 ]. Despite the urgent need for new antibiotic therapies, the pace of antibiotic discoveries has noticeably slowed down in recent decades due to scientific challenges and inadequate financial incentives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial contamination and infections result in over 30% of death worldwide 1,2 . Currently, there are more challenges in the clinical treatment of infectious diseases, due to the abuse or misuse of antibiotics, drug tolerance, and the building of pathogenic biofilm, leading to serious clinical issues and even death 3,4 . The studies by the World Health Organization (WHO) indicated that current antibiotics will fail to control pathogens in the next 20 years 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Currently, there are more challenges in the clinical treatment of infectious diseases, due to the abuse or misuse of antibiotics, drug tolerance, and the building of pathogenic biofilm, leading to serious clinical issues and even death. 3,4 The studies by the World Health Organization (WHO) indicated that current antibiotics will fail to control pathogens in the next 20 years. 5 Therefore, developing nextgeneration antimicrobial strategy to overcome these challenges we faced and combat infections is an unmet clinical need.…”
Section: Introductionmentioning
confidence: 99%